Constructing WHERE TO-Based Learning Activities: Escalating Competencies of Guru Penggerak Batch 10 in Medan City - Suci Perwita Sari; Ismail Saleh Nasution; Mawar Sari (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Teacher competency scores in Indonesia remain suboptimal, with an average score of 57 out of 100 in 2019. Specifically, Indonesia's teacher quality ranked 14th out of 14 developing countries according to UNESCO's 2016 GEM Report. To address these challenges, the Ministry of Education and Culture launched the Guru Penggerak program to enhance educational quality through student-centered learning and professional development. This study aims to improve the professional competencies of Guru Penggerak Batch 10 teachers in Medan City by constructing teaching modules using the WHERE TO framework within the context of differentiated learning and the Merdeka Curriculum. The research utilized a one-shot pretest-posttest group design conducted over two cycles. Participants included Batch 10 prospective Guru Penggerak teachers who underwent workshops and intensive mentoring. Data were collected via performance tests focusing on lesson plan design and analyzed using an independent T-test. Quantitative analysis revealed a significant improvement in teacher competencies, with average scores reaching 88 after two cycles. Statistical testing yielded a significance value of 0.000 (p < 0.05), indicating that the WHERE TO framework significantly impacts competency escalation. The framework encompassing Where, Hook, Explore, Reflect, Evaluate, Tailored, and Organized effectively addressed gaps in systematic instructional design and student-centered sequencing. The construction of WHERE TO-based learning activities serves as an effective integrative mechanism for developing multiple teacher competency domains, including curriculum knowledge, planning, and assessment. This approach fosters innovative thinking and professional autonomy among teachers in the Medan City region.